(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Low back pain of pelvic girdle dysfunction origin is most prevalent among all age group,hence there is constant need of updates in diagnosis and therapeutic approaches,manual physiotherapy gained an adequate importance in addressing pelvic girdle dysfunctions,with an objective of understanding the awareness of pelvic girdle dysfunctions among the clinicians and students, a self-administered questionnaire was designed and administered in pre-conference workshop pelvic girdle dysfunction dogmas in diagnosis and approach at SRM college of physiotherapy SRM Institute of Science and technology Chennai India,based on the response and through the statistical analysis it was found that the awareness was lacking and there was also need to focus on the clinicians and student community towards pelvic girdle dysfunctions and its basics, this may be beneficial in enhancing better patient care services and evidence in framing up clinical practice.